Pseudo Ricci-Symmetric (LCS)n-Manifolds (Global Journal of Science Frontier Research, 2017)
The present paper deals with the study of pseudo Ricci symmetric properties on (LCS)n-manifolds. Here we study generalized pseudo Riccisymmetric, almost pseudo Riccisymmetric and semi pseudo Ricci-symmetric (LCS)n-manifolds and obtained some interesting results.
Keywords: Lorentzian metric; (LCS)n-manifold; generalized pseudo riccisymmetric; almost pseudo riccisymmetric; semi pseudo ricci-symmetric